Microbially-mediated fossil-bearing carbonate concretions and their significance for palaeoenvironmental reconstructions: A multi-proxy organic and inorganic geochemical appraisal - Plet, Chloe; Grice, Kliti; Pages, A.; Ruebsam, W.; Coolen, Marco; Schwark, Lorenz (Elsevier, 2016)
Carbonate concretions are widespread within the geological record. However, the lack of recent known analogues creates a need for novel approaches to unravel the major microbial players involved in concretion formation and establish their suitability as palaeoenvironmental recorders. Here, we used a combination of geochemical and geological techniques to study two pyritiferous calcite concretions and compared the results with their host sediment (Toarcian “Posidonia Shale”, 183 Ma, SW-Germany). The 13C-depleted nature of the concretion bodies, with average values of d13Ccarb (-14.8‰), d13Corg (-32.4‰), and d13Cn-alkanes (-34.9‰), indicates that sulphate-reducing bacteria (SRB), played amajor role in the concretion growth and preservation of the nucleus via the rapid decomposition of organic matter (OM). However, Rock-Eval analyses from both concretions revealed elevated hydrogen indices (HI) in the body and lowHI values at the rim. These values suggest that most of the microbial activity did not occur in the concretion body but rather at the rim and at the surface of the nuclei, which generally supports the exceptional preservation of OM in carbonate concretions. Furthermore, enrichment in euhedral pyrite in the concretion rims suggests they were formed through increased activities of iron reducing (FeR) bacteria coupled to a decrease of SRB activity leading towards conditions more favourable to the direct precipitation of pyrite. Despite low d13C values, the known lipid biomarkers such as acyclic extended isoprenoids or 3ß-methyl-hopanes did not reveal evidence of an active methane cycling. The present study emphasises the crucial role of carbonate concretion in OM preservation and highlights their great potential as palaeoenvironmental recorders.